Regulation of HLA class II expression and its role in autoimmune disease. - Feldmann, M (1987)
Excessive HLA class II expression is found on the target tissues of the majority of human autoimmune diseases, together with activated (interleukin 2 receptor-expressing) T lymphocytes, suggesting that the target tissues act as antigen-presenting cells for infiltrating autoreactive cells, which in turn produce molecules that maintain class II expression. This vicious cycle has been shown to operate in Graves' thyroiditis, because interferon-gamma (IFN-gamma) induces class II expression on thyrocytes, and thyrocytes expressing class II antigens present their autoantigens to T cells cloned from thyroid tissue of Graves' disease patients. These results led us to consider whether the same mechanisms operate in other autoimmune diseases. In investigations into class II induction in other cell types we found that IFN-gamma is not the only regulator of HLA class II expression and that synergy exists among mediators regulating class II differentially on different cell types. This concept makes it possible to envisage selective diminution of class II antigens on target tissues without loss of class II on antigen-presenting cells. The study of mediators regulating class II expression on cells in vitro led us to ask whether the appropriate regulator molecules are important in disease states. To investigate this question we have developed the use of cDNA probes to analyse the expression of lymphokines, other cytokines, and receptors in small local biopsy samples of tissue from patients with autoimmune diseases. Results obtained so far indicate that mRNAs for many lymphokines are present in synovial fluid cell samples from patients with rheumatoid arthritis.